The Anti-Inflammatory Effect of ACE-I/ARBs Drug on hs-CRP and HDL-Cholesterol in CKD Patient - Muhammad Iqbal Mubarok; Maftuchah Rochmanti; Mochamad Yusuf; Mochammad Thaha (Indian Journal of Forensic Medicine & Toxicology, 2021)
Chronic kidney disease (CKD) is progressive disease that closely related to the chronic inflammatory process.Angiotensin-Converting Enzyme Inhibitor (ACE-I)/Angiotensin Receptor Blockers (ARBs) is the main therapy in the management of CKD, based on the recent sudies stated that this drug have pleiotropic effects as anti-inflammation.The aim of this study is tosee the interaction of hs-CRP and HDL-Cholesterol to prove the role of ACE-I/ARBs as an anti-inflammatory treatment for CKD patient. In this study we compared hsCRP, HDL Cholesterol and HDL Cholesterol /hs-CRP ratio levels in CKD patients who consumeand do not consumeACE-I/ARBs. Forty eight samples of CKD patients were taken randomly and then separated into two group based on their consumption of ACE-I/ARBs, each group have 24 samples.There were significantly different of mean of hs-CRP, HDL Cholesterol, and HDL Cholesterol/hs-CRP ratio between group, the mean concentration of hs-CRP in the ACE-I/ARBs group was significantly lower than in non-ACE-I/ARBs group (1,48±0,81 vs 4,19±4,02; P= 0.038),the mean of HDL (48,95±13,05vs 41,50±12,31; P= 0,048).There were negative correlation between HDL Cholesterol and hs-CRP, positive correlation between HDL Cholesterol/hs-CRP ratio and eGFR.This result indicate that hs-CRP and HDL-Cholesterol monitoring very important in CKD patient.